A comprehensive fractal approach in determination of the effective thermal conductivity of gas diffusion layers in polymer electrolyte membrane fuel cells - Azizan, Mohd Fikri (2017)
The challenges in the fuel cell industry is to produce the efficient thermal and water management for accurate determination of the effectiveness thermal conductivity of gas diffusion layers (GDL) used in polymer electrolyte membrane fuel cells (PEMFC‟s). This is one of the factors affecting the durability of a fuel cell and need to get a solution to minimize costs and optimize the use of electrodes and cells. The main objectives of this research focus on the capability of the fractal approach for estimation the effectiveness of thermal conductivity of gas diffusion layer. Moreover, on this research also to propose modified fractal equations in determination of the effective thermal conductivity of GDL in PEMFCs based on previous study. Other objectives in this study are demonstrated the thermal conductivity of GDL treated with PTFE contents by using through-plane thermal conductivity experiment method. The through-plane measurement (experiment method) has been used in estimating through-plane thermal conductivity of the GDL. Thermal resistance for GDL also has been investigated under compression pressure 0.1 MPa until 1.0 MPa. In fractal equation, the determination of tortuous and pore fractal dimension can be done by using Scanning Electron Microscopy (SEM) method. Determination of effectiveness thermal conductivity using of fractal equation with slightly modified. In findings, it was found that fractal equation have been modified and measured on the GDL parameter characteristics. It was shown that the value of the effectiveness thermal conductivity of the sample using fractal approach is in good agreement with the experimental value. Finally, all the effective thermal conductivity measured by experimental and fractal approach have been determined with the variant temperature and compression pressure to show the validation result between of this two methods.